The Attentional Capture Debate: When Can We Avoid Salient Distractors and When Not? - Theeuwes, Jan (Journal of cognition, 2023)
There has been a long-standing debate concerning whether we are able to resist attention capture by salient distractors. The so-called "signal suppression hypothesis" of Gaspelin and Luck (2018) claimed to have resolved this debate. According to this view, salient stimuli "naturally attempt to capture attention", yet attention capture may be prevented by a top-down inhibitory mechanism. The current paper describes the conditions in which attention capture by salient distractors can be avoided. Capture by salient items can be avoided when the target is non-salient and therefore difficult to find. Because fine discrimination is needed, a small attentional window is adapted resulting in serial (or partly serial) search. Salient signals outside the focused attentional window do not capture attention anymore not because they are suppressed but because they are ignored. We argue that in studies that have provided evidence for signal suppression, search was likely serial or at least partly serial. When the target is salient, search will be conducted in parallel, and in those cases the salient singleton cannot be ignored nor suppressed but instead will capture attention. We argue that the "signal suppression" account (Gaspelin & Luck, 2018) that seeks to explain resistance to attentional capture has many parallels to classic visual search models such as the "feature integration theory" (Treisman & Gelade, 1980), "feature inhibition" account (Treisman & Sato, 1990), and "guided search" (Wolfe et al, 1989); all models that explain how the serial deployment of attention is guided by the output of earlier parallel processes.